The Conditions and Obstacles for Apostasy Punishment in Islamic Sharī’ah: A Review of different opinions of Muslim schools of thoughts - Anees ur Rehman Siddiqui; Dr. Riaz Ahmed Saeed (jihat-ul-islam, 2023)
Apostasy has always been the most critical topic in Islam. Apostasy is a major issue that threatens religious integrity. The punishment of an apostate is harsh due to his leaving Islam and blaming it. According to Islamic law, apostasy is a punishable crime, and those who commit it should be sentenced to death. This penalty is described by the Book of Allah, Holy Quran, the Prophet’s (PBUH) Sunnah and the consensus of the Muslim Ummah. More than a dozen verses of the Quran and numerous Ahādīth of the Prophet Muhammad (PBUH) have been discussed regarding the penalty of apostasy. In the same way, apostasy has some rules and conditions that must be met, and some obstacles must be removed. According to Islamic Sharī’ah, apostasy is only possible if a person is smart, has reached puberty, has a clear intention, and uses good judgment. In this study, efforts are made to elaborate the terms and conditions for the punishment of apostasy in different Muslim jurisprudence schools of thoughts. Analytical research methodology has been adopted in this study with a qualitative research approach. A child who commits apostasy is imprisoned until the child reaches the age of maturity. The child will not be put to death for leaving the faith. Only people who leave the faith while fully aware will be put to death. If a person is forced to commit apostasy, they will not be punished. On behalf of this study, it is recommended that the Islamic laws of apostasy be compared with contemporary international laws in modern nations’ Islamic states regarding freedom of religion and human rights.